Peran Mahasiswa pada Kegiatan Asistensi Mengajar dalam Mengasah Keterampilan Berbicara Siswa SMAS Al-Hikam melalui Lomba Orasi - Reyadi, Abad; Agustin, Laila Dwi; Isnainih, Lusiatul; Nikmah, Zulfa Ulin; Setyawan, Arief (Universitas Negeri Gorontalo, 2025)
This study uses a case study of Al-Hikam Senior High School to illustrate the role of student teaching assistants in honing students' speaking skills through oration competitions. Speaking skills are an important skill that must be learned early amidst intense global competition. Students have the opportunity to learn directly from fellow students through the teaching assistant program, which emphasizes speaking skills such as rhetoric, material mastery, and self-confidence. This study found that teaching assistants at Al-Hikam Senior High School can encourage students to think more critically and be bold in expressing their opinions. This was discovered through observation methods and the implementation of oration competitions. The program also increased students' confidence in public speaking. The results showed that students who are actively involved in the teaching assistant program can make learning fun and relevant, thereby fostering students' interest in deepening better communication skills.